PROS AND CONS LAW OF CREATION BASED ON LEGAL SOCIOLOGY ANALYSIS - Sigit Gunawan; Muhammad Rasyid Ridho; Amiludin Amiludin (Jurnal Hukum Replik, 2020)
The Omnibus Law of the Job Creation Act initiated by President Joko Widodo during the second term of office is one of the largest bureaucratic simplification projects ever undertaken by the Indonesian nation. The purpose of the Job Creation Law is to stimulate investment growth to support the country's economy is facing an increasingly competitive international economic climate. The Job Creation Law is a bureaucratic simplification package in the form of changes to laws in various lines, such as investment, labor, and spatial planning. As a form of the legal product discussed and ratified by the executive and legislative powers, the Job Creation Law also does not escape the responsibilities of the people who support and reject it. Strong rejection is expressed in the form of protests both in writing and using mass actions, mostly carried out by workers, environmental activists, and academics. Sociology of law as a science that studies the interrelationship between law and social phenomena that occur empirically in society can be used as a tool of analysis to determine how the effectiveness of the Job Creation Law as a tool of social control, social engineering. The better the public's response to a legal product, then sociologically, the product can be used for its intended purpose. Keywords: Omnibus Law, Job Creation Law, Sociology of Law